Genetic insights and therapeutic avenues: unraveling the role of polyunsaturated fatty acids as mediators between hypothyroidism and Von Willebrand disease through Mendelian randomization - Zhou, Wenting; He, Rui; Ou, Ruwei (Frontiers in Genetics, 2025)
BackgroundPrevious observational studies have shown that Hypothyroidism is associated with Von Willebrand Disease (VWD), but the causal relationship has not been confirmed because of conflicting findings and confounding by mixing factors. There are also some studies suggesting that polyunsaturated fatty acids (PUFA) may be one of the potential mediators. In this study, we used a Mendelian randomization study to analyze the causal relationship between Hypothyroidism and VWD and to investigate whether polyunsaturated fatty acids mediate the effects of Hypothyroidism on VWD.MethodsUsing a large publicly available genome-wide association study of predominantly European ancestry to obtain data on Hypothyroidism, VWD, and PUFA, we conducted a two-sample Mendelian randomization study to assess the causal relationship between Hypothyroidism and VWD and assess the potential role of Polyunsaturated fatty acids in mediating the causal pathway between Hypothyroidism and VWD. Finally, we also inferred reverse causality between VWD and Hypothyroidism. Inverse variance weighting (IVW) was the primary analytical method.ResultsWe found that Hypothyroidism may be negatively causally associated with the development of VWD and that PUFA have a role in mediating role in this process (the ratio of the mediating effect: 24.33%). The causal effects of Hypothyroidism and PUFA on VWD remained significant (p < 0.05) after correction of each other by MVMR.ConclusionOur study unveils a novel negative correlation between hypothyroidism and VWD, further enriched by the discovery of partial mediation by PUFA. This groundbreaking finding not only advances our comprehension of VWD etiology but also opens promising avenues for its control and treatment. By elucidating the intricate interplay between hypothyroidism, PUFA, and VWD, our research pioneers a paradigm shift in therapeutic approaches, offering fresh perspectives for the management of this complex disorder.